If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + -8 = 76 + -7x Reorder the terms: -8 + 5x = 76 + -7x Solving -8 + 5x = 76 + -7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '7x' to each side of the equation. -8 + 5x + 7x = 76 + -7x + 7x Combine like terms: 5x + 7x = 12x -8 + 12x = 76 + -7x + 7x Combine like terms: -7x + 7x = 0 -8 + 12x = 76 + 0 -8 + 12x = 76 Add '8' to each side of the equation. -8 + 8 + 12x = 76 + 8 Combine like terms: -8 + 8 = 0 0 + 12x = 76 + 8 12x = 76 + 8 Combine like terms: 76 + 8 = 84 12x = 84 Divide each side by '12'. x = 7 Simplifying x = 7
| 0.81-0.1v=2.6v-2.4v | | 10=.04v^2+1.1v | | -2(3r-9)-4(r-6)-13r= | | 3x+x+16=62 | | 2=7+w | | .04x^2+1.1x-2=0 | | 0.2w-0.15=0.875-0.4 | | 1/2(4x+2)=4x+8 | | 75=-5(-3-4x) | | 4k-40=-8 | | -2=3x | | 6(z-2)+4=10 | | 3(3x-5)-7x=25 | | -2(m-40)=-6m | | -2(x-1)17=12 | | x^2+2x-28=0 | | 8(7+y)=-24 | | -2(x-1)-17=12 | | 16-8y=4 | | 8(m+5)=-2+8m | | -6x+12=2(3x-6) | | 4(x-2)+5=3+2x-6 | | 12=8-w | | 7+6(6z+7)=-2(-4z-2)+2 | | 2+3=4-6 | | x-x(.33)=284.75 | | 3x+3+x=7 | | 3(4x-3)=3+2(5x-3) | | 1a-30=2a+6 | | x+3=2.8 | | x-.33=284.75 | | 2-5(-6y-2)=-2(-4y-3)-3 |